Is the use of standardized patients more effective than role-playing in medical education? A meta-analysis - Xiao, Jingyuan; Fu, Xinjian (Frontiers in Medicine, 2025)
AimThis study aimed to compare the effectiveness of using Standardized patients (SPs) and Role-playing (RP) in medical education. It is crucial to understand the differences in the effects of SPs and RP. However, the existing measurement results are varied, and the findings lack robustness.MethodsWe collected the results of various experiments and conducted a meta-analysis. In total, 10 articles and 27 effect sizes were included in the analysis, involving 721 students.ResultsThe meta-analysis results showed that compared to the RP method, using SPs significantly improved students’ self-confidence (effect size = 0.415). However, in other aspects, the two methods showed similar outcomes. We observed that the effectiveness of SPs teaching methods increased over time.ConclusionSPs effectively enhance students’ self-confidence by simulating diverse roles, situations, and real-world work scenarios. This study provides a comprehensive comparative perspective on RP and SPs.